Meningocele and procephalic hypoplasia in a calf in the Sertão da Paraíba - Oliveira, Artefio Martins de; Souto, Erick Platiní Ferreira; Garcia, Dlean da Silva; Dantas, Antonio Flávio Medeiros (Seven Editora, 2023)
We describe a case of meningocele, cranioschisis, and procephalic hypoplasia in a calf in the semi-arid region of Paraíba, Northeastern Brazil. A three-day-old male calf with no defined racial pattern was referred for clinical evaluation at the Veterinary Hospital of the Federal University of Campina Grande with an increase in fluctuating volume, completely covered by intact skin located in the frontal region of the head. Due to the unfavorable prognosis, the animal was euthanized. At necropsy, herniation of the meninges was observed through an opening in the midline of the frontal bone of the skull containing approximately 1300 ml of reddish fluid. The brain presented incomplete formation, with the absence of the telencephalic hemispheres, but with a well-formed brainstem, a condition consistent with procephalic hypoplasia. Histologically, congestion was observed in the ventral part of the telencephalon and caudate nuclei, and areas of hemorrhage, corpora amylacea, discrete mineralization, and axonal spheroids in the neuropile. Meningocele and cranioschisis are rare malformations, which are always associated, and have an unclear etiology in most cases. DOI:https://doi.org/10.56238/alookdevelopv1-189